Validating the measurement of components of commitment in a portuguese sample - Rodrigues, D. (2015)
This study aimed at adapting and validating the Measurement of Components of Commitment scale (MCC; Johnson et al. in J Marriage Fam 61:160–177, 1999) in a sample of 335 Portuguese individuals, varying in sexual orientation and type of romantic relationship (single, civil union, married). Results suggest adequate construct validity and reliability. Principal axis factoring and confirmatory factorial analysis supported Johnson et al. (1999) proposed tripartite structure: personal commitment referring to positive feelings towards the partner (three factors); moral commitment referring to a sense of moral obligation to maintain the relationship (three factors); structural commitment referring to the perception of external barriers preventing relationship termination (four factors). Convergent validity results further suggest the MCC’s distinctiveness regarding other measures of commitment, by showing personal, but not moral or structural, commitment, to correlate with the Investment Model Scale (Rusbult et al. in Personal Relationships 5:357–387, 1998), defining commitment as a unitary construct pertaining a general long-term orientation and intent to persist in the relationship, and psychological attachment towards the partner. Finally, the MCC proved sensible across different types of romantic relationship, cohabitation status and relationship duration, further extending the scale’s original results and evidences on construct validity. We discuss MCC’s relevance to academics and professionals studying romantic relationships.